Properties of BC6N monolayer derived by first-principle computation: Influences of interactions between dopant atoms on thermoelectric and optical properties. (15th November 2021) - Abdullah, Nzar Rauf; Abdullah, Botan Jawdat; Tang, Chi-Shung; Gudmundsson, Vidar
Abstract: The properties of graphene-like BC 6 N semiconductor are studied using density functional theory taking into account the attractive interaction between B and N atoms. In the presence of a strong attractive interaction between B and N dopant atoms, the electron charge distribution is highly localized along the B-N bonds, while for a weaker attractive interaction the electrons are delocalized along the entire hexagonal ring of BC 6 N. Furthermore, when both B and N atoms are doped at the same site of the hexagon, the breaking of the sub-lattice symmetry is low producing a small bandgap. In contrast, if the dopant atoms are at different sites, a high sub-lattice symmetry breaking is found leading to a large bandgap. The influences of electron localization/delocalization and the tunable bandgap on thermal behaviors such as the electronic thermal conductivity, the Seebeck coefficient, and the figure of merit, and optical properties such as the dielectric function, the excitation spectra, the refractive index, the electron energy loss spectra, the reflectivity, and the optical conductivity are presented. An enhancement with a red shift of the optical conductivity at low energy range is seen while a reduction at the high energy range is found indicating that the BC 6 N structure may be useful for optoelectronic devices in the low energy, visible range.